The modeling of laboratory information systems in higher education based on enterprise architecture planning (EAP) for optimizing monitoring and equipment maintenance - Yahya Nur Ifriza; Trisni Wulandari Veronika; Trisni Suryarini; Antonius Supriyadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The laboratory is a place to conduct scientific research, experiments, measurements, or scientific training. FMIPA UNNES has several laboratories distributed in each department to support student lectures. Through the implementation of practicum in the laboratory, students are expected to be able to find a concept, foster scientific attitudes, and critical thinking skills. Good laboratory management is expected to be able to utilize laboratory resources effectively and efficiently. Laboratory equipment must be ensured to function properly and be ready to be used for practicum. To support this, it is necessary to monitor the condition of the equipment and immediately repair the equipment if any damage is found. The current obstacle is monitoring tool repairs manually, so there are shortcomings such as poor documentation, and equipment conditions that cannot be monitored online. In this study, an information system for monitoring the maintenance of laboratory equipment in the departments in the FMIPA UNNES environment will be built. The research method begins with a literature study, initial data collection and observation, EAP-based system design, system testing, system analysis, and system evaluation. This study uses the SDLC (System Development Life Cycle) approach which is used to develop a product for the Monitoring Information System for the Maintenance of Laboratory Equipment. Testing is done using black box testing. From the results of development and testing, it can be concluded that the system can be used to simplify the process of managing laboratory equipment with a UAT value of 88% suitable for use.